Necrotizing fasciitis following episiotomy in a woman with Hailey-Hailey disease: A case report - Heba Abu Saleem; Osama Al-Natour; Ismaiel Abu Mahfouz; Mohd Abu Assamen; Said Al-Natour (Elsevier, 2022)
A healthy 25-year-old primiparous woman had an uncomplicated pregnancy and spontaneous vaginal delivery with mediolateral episiotomy. Twenty-four hours postpartum, she developed increasing perineal pain and swelling. Initial examination showed a localized erythema and tissue oedema at the episiotomy site. The woman was admitted to hospital for management of the infected hematoma at the site of the episiotomy. Thereafter, she was started on intravenous antibiotics, and exploration under anaesthesia was planned. The woman's medical condition deteriorated rapidly, and necrotizing fasciitis (NF) was strongly suspected. Therefore, aggressive medical and surgical management was undertaken, including broader-spectrum antibiotics and multiple surgical debridement. A biopsy of the debrided tissue showed acantholysis and dyskeratosis, which are features of Hailey-Hailey disease of the skin (familial benign chronic pemphigus), a rare condition. The woman eventually had a V-Y advancement fascial flap and made a complete recovery. In this case report, the details of the development of NF in a woman who was found to have Hailey-Hailey disease are discussed.